Soft-information flipping approach in multi-head multi-track BPMR systems - C. Warisarn; W. Busyatras; L. M. M. Myint (My University, 2017)
Inter-track interference is one of the most severe impairments in bit-patterned media recording system. This impairment can be effectively handled by a modulation code and a multi-head array jointly processing multiple tracks; however, such a modulation constraint has never been utilized to improve the soft-information. Therefore, this paper proposes the utilization of modulation codes with an encoded constraint defined by the criteria for soft-information flipping during a three-track data detection process. Moreover, we also investigate the optimal offset position of readheads to provide the most improvement in system performance. The simulation results indicate that the proposed systems with and without position jitter are significantly superior to uncoded systems.
Keywords: Modulation (music); Patterned media; Code (set theory); Cellular Automata and Applications